Financial Due Diligence in Increasing Company Value Through Banking Mergers and Acquisitions During COVID-19 - Arnika Dwiyanti; Ludovicus Sensi Wondabio (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2023)
The COVID-19 pandemic took an enormous effect on the company's ability to survive, and the most popular way to survive was through mergers and acquisitions (M&A), which in Indonesia, was triggered by the stipulation of Financial Services Authority Regulation (POJK) Number 12/POJK.03/2020 on Commercial Bank Consolidation. Thus, M&A activities in the Indonesian Banking industry increased, concerning the role of engaged auditors as practitioners who have competency in conducting financial due diligence (FDD) through critical aspects that are directly and not directly affected by pandemic conditions. This research focused on FDD process evaluation to support the aims of reducing failure of M&A by confirming the veracity of data, so it could prevent loss and create value for shareholders. To understand the practice, concurrent mixed method research was applied to the acquisition case of PT Bank Mayora (Mayora) by PT Bank Negara Indonesia Tbk (BNI) through interviews and documentation. The evaluation of this research is not only within the scope of M&A in previous research but carries the banking industry's FDD to comply with POJK during the COVID-19 pandemic. The study finds some new aspects to contribute wider points of view for auditors in conducting FDD, including technology-based FDD development of processes and procedures.